Diritti e democrazia nella dimensione spirituale - Giuliano Savina (Democrazia e Diritti Sociali)
The aim of this paper is to trace a common thread between some sources of the Catholic Church’s magisterium, from which to discern the vocabulary of the Church of Vatican II. This vocabulary reveals, through the language of magisterial documents, the self-awareness of the conciliar Church, precisely through the overcoming of a limiting confessional catholicity with the formulation of the Catholic principles of ecumenism and interreligious dialogue. The turning point of Vatican II focuses on the Humus from which each person’s religious questioning arises, to be grasped in the processes of human educability of which the Church is by vocation the custodian and promoter, for a commitment that fosters social cohesion.